ANALISIS HUKUM PENGGUNAAN FREKUENSI RADIO TANPA IZIN BERDASARKAN UU NO.36 TAHUN 1999 TENTANG TELEKOMUNIKASI (Studi putusan Pengadilan Negeri Salatiga Nomor 91/Pid.B/2013/PN.Sal) - Hanawi Aananda Putra Sitohang; Muhammad Hamdan; Mahmud Mulyadi; Jelly Leviza (Universitas Sumatera Utara, 2016)
ABSTRACT The use of radio frequencies must obtain permission from the government, before obtaining permission still broadcasting, radio broadcasting institutions must go through the trial broadcast period of 6 (six) months. Broadcasting licenses that have been granted are prohibited transferred (given, sold, or otherwise transferred) to another party (other legal entities or other persons). While the act of taking without permission outside the consent or will of the owner (against the law) called the theft of the book of criminal law. The element Regulation frequency use without the permission of